2013
DOI: 10.1371/journal.pone.0059004
|View full text |Cite
|
Sign up to set email alerts
|

A Pareto-Optimal Refinement Method for Protein Design Scaffolds

Abstract: Computational design of protein function involves a search for amino acids with the lowest energy subject to a set of constraints specifying function. In many cases a set of natural protein backbone structures, or ''scaffolds'', are searched to find regions where functional sites (an enzyme active site, ligand binding pocket, protein -protein interaction region, etc.) can be placed, and the identities of the surrounding amino acids are optimized to satisfy functional constraints. Input native protein structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
267
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(269 citation statements)
references
References 14 publications
2
267
0
Order By: Relevance
“…21 Recently, Arpino et al [16] experimentally determined the functional consequences 22 of single deletions in enhanced green fluorescent protein (eGFP) by systematically 23 deleting individual residues from eGFP and then assaying for function. Similar to 24 observations from computational studies, most functional deletion mutants were located 25 in unstructured loop regions, as opposed to in highly structured regions comprised of 26 β-sheets and α-helices. In addition, Arpino et al observed that non-functional mutants 27 were more likely to occur in buried regions than were functional mutants [16].…”
supporting
confidence: 73%
“…21 Recently, Arpino et al [16] experimentally determined the functional consequences 22 of single deletions in enhanced green fluorescent protein (eGFP) by systematically 23 deleting individual residues from eGFP and then assaying for function. Similar to 24 observations from computational studies, most functional deletion mutants were located 25 in unstructured loop regions, as opposed to in highly structured regions comprised of 26 β-sheets and α-helices. In addition, Arpino et al observed that non-functional mutants 27 were more likely to occur in buried regions than were functional mutants [16].…”
supporting
confidence: 73%
“…The substrate molecule as well as side chains forming the active site were kept flexible during the docking trials: Ile-6, His-8, Asp-9, Lys-12, Thr-34, Thr-36, Thr-37, Ser-54, Asp-60, Phe-77, His-87 and Val-91. Interestingly, successful docking results were obtained only for the receptor model which was relaxed using Rosetta application (72). Relax protocol in Rosetta performs a simple all-atom model refinement in the Rosetta force-field which searches the local conformational space around the starting structure (RMSD calculated for C atoms forming the MgsA hexamer amounted to 0.06 Å).…”
Section: Computational Modellingmentioning
confidence: 99%
“…2 The Pareto optimal set is depicted for a bi-objective problem f 1 , f 2 , where non-dominated solutions (red) cannot be further improved for f 1 without degrading f 2 or vice versa. Other solutions (gray) may be improved along either objective without compromising the other applied to the design of stabilizing mutations to proteins that minimally disrupt the native structure, concurrently optimizing energy and RMSD from the initial structure (Nivón et al 2013). State-of-the-art multi-objective optimization evolutionary algorithms such as SMS-EMOA have been applied to the design of peptide ligands that bind with reasonable affinity and selectivity for a specific isoform of 14-3-3 proteins (Sanchez-Faddeev et al 2012).…”
Section: Pareto Optimalitymentioning
confidence: 99%